2019
DOI: 10.1111/tbed.13112
|View full text |Cite
|
Sign up to set email alerts
|

Foot‐and‐mouth disease outbreaks due to an exotic serotype Asia 1 virus in Myanmar in 2017

Abstract: In January 2017, two villages located in Rakhine State of Myanmar reported clinical signs in cattle suggestive of foot‐and‐mouth disease virus (FMDV) infection. Laboratory analysis identified the outbreak virus as FMDV serotype Asia 1, which represented the first detection of this serotype in Myanmar since 2005 and in the region of South‐East Asia (SEA) since 2007. Genetic analysis revealed that the outbreak virus was different from historical viruses from Myanmar and was more closely related to viruses circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Underlying evolutionary insights for the genesis of novel lineage and spatial dynamics related to G‐IX might occur due to steady abstruse transmission and viral diversity due to poor surveillance of this semi‐extinct virus type in recent years from Bangladesh. Notably, the possible chance and significant risk due to the intrusions of exotic and novel FMDV strains into previously non‐circulating zone for those viruses were demonstrated in a recent risk analysis study (Bo et al, ). Therefore, current FMD situation needs to be monitored closely, especially focusing on the entry and spread of this novel strain, which will give time to adjust vaccine compositions.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Underlying evolutionary insights for the genesis of novel lineage and spatial dynamics related to G‐IX might occur due to steady abstruse transmission and viral diversity due to poor surveillance of this semi‐extinct virus type in recent years from Bangladesh. Notably, the possible chance and significant risk due to the intrusions of exotic and novel FMDV strains into previously non‐circulating zone for those viruses were demonstrated in a recent risk analysis study (Bo et al, ). Therefore, current FMD situation needs to be monitored closely, especially focusing on the entry and spread of this novel strain, which will give time to adjust vaccine compositions.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the clade of G‐IX and its closest genetic lineage G‐VIII (Table S4) separated in the distance tree with an ND of > 5% demonstrating the presence of two separate lineages (Figure S2). Significantly, the most recent G‐VIII strain (MYA/3/2017) isolated from Myanmar in April 2017 (Bo et al, ) showed only ~ 90% nucleotide identity with strains of lineage G‐IX. Before the emergence of this lineage, lineage G‐VIII was sporadically circulating in Bangladesh and its neighbouring countries (Subramaniam et al, ; Ullah et al, ; WRLFMD, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the rate of change in the virus, as seen in the evolution of FMD viruses or the introduction of new viruses, outpaces vaccine development research, it will become more difficult to protect against the virus [22, 23]. In this respect, this study provided a framework for rapid development of new vaccines, proposing that the establishment of a more reliable method for vaccine development that surpasses the evolution rate of the virus can be a means to advance the vaccine research a step further [22, 23]. Thus far, the SAT serotype viruses are known to mainly infect cattle and African buffalos [2426].…”
Section: Discussionmentioning
confidence: 99%